How we love : discover your love style, enhance your marriage - Yerkovich, Milan; Yerkovich, Kay (WaterBrook, 2017)
Are you tired of falling into frustrating relational patterns in your marriage? Do you and your spouse fight about the same things again and again? Relationship experts Milan and Kay Yerkovich explain why the ways you and your spouse relate to each other go back to before you even met. Drawing on the powerful tool of attachment theory, Milan and Kay explore how your childhood created an “intimacy imprint” that affects your marriage today. Their stories and practical ideas help you: * identify your personal love style * understand how your early life impacts you and your spouse * break free from painful patterns that keep you stuck * find healing for the source of conflict, not just the symptoms * create the close, nourishing relationship you dream about. Revised throughout with all-new material, additional visual diagrams, and a revised accompanying workbook, this expanded edition of How We Love will bring vibrant life to your marriage. Are you ready for a new journey of love?